A DINÂMICA DO DESENVOLVIMENTO SOCIOECONÔMICO DOS MUNICÍPIOS DA REGIÃO DA AMARP EM SANTA CATARINA -BRASIL / THE DYNAMICS OF SOCIOECONOMIC DEVELOPMENT OF MUNICIPALITIES IN THE AMARP REGION IN SANTA CATARINA-BRAZIL - Nogueira Duarte, Vilmar (Informe GEPEC, 2023)
Este artigo analisou a dinâmica do desenvolvimento socioeconômico dos municípios integrantes da Associação dos Municípios do Alto Vale do Rio do Peixe - AMARP - SC entre os anos de 2005 e 2016. Para a análise dos municípios adotou-se o Índice Firjan de Desenvolvimento Municipal (IFDM) e como parâmetro metodológico o “Informe sobre Desarrollo Humano” publicado no México em 2002, o qual classifica os municípios em: a) tendendo ao crescimento; b) tendendo ao desenvolvimento; c) círculo vicioso; e d) círculo virtuoso. A análise foi realizada em duas etapas. A primeira mostra a dinâmica da população, do emprego formal e do IFDM dos municípios de abrangência da AMARP. A segunda utiliza duas abordagens analíticas: a intrarregional, que compara o IFDM de cada município da AMARP com a média própria da região; e a inter-regional, que compara o IFDM de cada município da região com a média do estado catarinense como um todo. Os resultados mostram uma melhor condição de desenvolvimento socioeconômico dos municípios da região quando comparados com a média da própria região, ao contrário de quando comparados com a média estadual, em que as desigualdades municipais são mais evidentes, com um elevado número de municípios na condição de subdesenvolvimento. Abstract : This article analyzed the dynamics of the socioeconomic development of the municipalities that are part of the Association of Municipalities of Alto Vale do Rio do Peixe - AMARP - SC between the years 2005 and 2016. For the analysis of the municipalities, the Firjan Index of Municipal Development (IFDM) was adopted and as a methodological parameter the “Informe sobre Desarrollo Humano” published in Mexico in 2002, which classifies municipalities in: a) tending to growth; b) tending to development; c) vicious circle; and d) virtuous circle. The analysis was carried out in two stages. The first shows the dynamics of population, formal employment and IFDM in the municipalities covered by AMARP. The second uses two analytical approaches: the intraregional one, which compares the IFDM of each municipality in the AMARP with the average for the region; and the interregional one, which compares the IFDM of each municipality in the region with the average for the state of Santa Catarina as a whole. The results show a better condition of socioeconomic development of the municipalities in the region when compared with the average of the region itself, as opposed to when compared with the state average, where municipal inequalities are more evident, with a high number of municipalities in the status of underdevelopment.